Hemolysis following Intravenous Immunoglobulin Therapy - Adverse effect to remember about - Iwaniuk, Sebastian; Maciejewski, Ignacy; Kowalik, Kinga; Szypulski, Szymon; Zielińska, Aleksandra; Michalska, Maria; Tylczyńska, Natalia; Tylczyńska, Kinga; Skiba, Zuzanna; Skiba, Jakub (Journal of Education, Health and Sport, 2025)
Intravenous immunoglobulin (IVIG) therapy has become a cornerstone in the treatment of various immunological and neurological disorders. Its origins trace back to the pioneering work of Emil Adolf von Behring and Shibasaburo Kitasato in the late 19th century.[1][2] Over time, advancements in immunoglobulin preparation techniques and the shift from animal-derived to human-derived serum have significantly improved IVIG safety and efficacy.[1][3] By the late 20th century, IVIG was recognized as a standard therapy for conditions such as primary immunodeficiencies (PID) and Kawasaki disease.[4] Today, IVIG is widely used for PID, secondary immunodeficiencies, primary immune thrombocytopenia, Guillain–Barré syndrome, chronic inflammatory demyelinating polyneuropathy, and post-transplant immunomodulation. [5][6][7][8][9][10] Despite its therapeutic advantages, IVIG can cause adverse effects, including flu-like symptoms, dermatological reactions, thromboembolic events, neurological disturbances, renal impairment, and hematological disorders like hemolysis.[11] Hemolysis, though often overlooked, can lead to unnecessary concern and treatment modifications. Its pathophysiology involves both intravascular and extravascular mechanisms, influenced by factors such as blood group, IVIG dosage, and manufacturing processes.[11] While severe hemolysis is rare, mild cases are more common and may prolong hospitalizations.[12] Raising awareness of IVIG-related hemolysis can improve patient management and therapeutic decision-making, ultimately optimizing clinical outcomes.